Geotechnical engineering for the preservation of monuments and historic sites : proceedings of the second International Symposium on Geotechnical Engineering for the Preservation of Monuments and Historic Sites, Napoli, Italy, 30-31 May 2013 - Bilotta, Emilio; International Symposium on Geotechnical Engineering for the Preservation of Monuments and Historic Sites 2013 : Napoli) (London : CRC Press, 2013)
All the traces of historic heritage are a fundamental part of our environment and reward us in the form of cultural enrichment, with the ability to have a positive effect both on our lifestyle and economy. Therefore, the preservation of ancient monuments, historic towns and sites has increasingly drawn the attention of public opinion, governmental agencies as well as consultants and contractors. This interest must be however carefully controlled and directed, since the conservation of monuments and historic sites is one of the most challenging problems of our age. Careless attempts at preserva.
-- Opening address -- Special lectures -- Papers.
"A balkema book."
Includes bibliographical references and index.
Keywords: Historic sites -- Conservation and restoration -- Congresses; Historic sites -- Conservation and restoration; Monuments -- Conservation and restoration -- Congresses; Monuments -- Conservation and restoration; Soil mechanics -- Congresses; Soil mechanics